2014
DOI: 10.2337/db13-1073
|View full text |Cite
|
Sign up to set email alerts
|

Orexinergic Activation of Medullary Premotor Neurons Modulates the Adrenal Sympathoexcitation to Hypothalamic Glucoprivation

Abstract: Glucoprivation activates neurons in the perifornical hypothalamus (PeH) and in the rostral ventrolateral medulla (RVLM), which results in the release of adrenaline. The current study aimed to establish 1) whether neuroglucoprivation in the PeH or in the RVLM elicits adrenaline release in vivo and 2) whether direct activation by glucoprivation or orexin release in the RVLM modulates the adrenaline release. Neuroglucoprivation in the PeH or RVLM was elicited by microinjections of 2-deoxy-D-glucose or 5-thio-D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 45 publications
5
51
0
Order By: Relevance
“…This is consistent with our previous work comparing spinal and hypothalamic DSAP injections (10,35) and with results using various other experimental approaches indicating that spinally projecting catecholamine neurons mediate the adrenal medullary response to glucose deficit (60,61). Orexin neurons also project spinally (62) and recent evidence suggests an independent role for these projections in controlling blood glucose (63). Accordingly, orexin neurons that project directly to the spinal cord might contribute to control of blood glucose in PVH-or PeFLH-DSAP-injected rats during glucoprivation.…”
supporting
confidence: 91%
“…This is consistent with our previous work comparing spinal and hypothalamic DSAP injections (10,35) and with results using various other experimental approaches indicating that spinally projecting catecholamine neurons mediate the adrenal medullary response to glucose deficit (60,61). Orexin neurons also project spinally (62) and recent evidence suggests an independent role for these projections in controlling blood glucose (63). Accordingly, orexin neurons that project directly to the spinal cord might contribute to control of blood glucose in PVH-or PeFLH-DSAP-injected rats during glucoprivation.…”
supporting
confidence: 91%
“…The fact that CPP blunting was prevented by concurrent systemic administration of a brain-penetrant orexin-1 receptor antagonist (25,42) strongly suggests that orexin neurons, which are found only in the PFH and LHA (12,43), are critical components of this response. In fact, we have shown that this same antagonist blunts the Epi response to IIH (37) in keeping with the known connections of PFH orexin neurons with brain stem sympathetic outputs (29) and polysynaptic inputs to the adrenal gland (21). Our results demonstrating a selective decrease in PFH, but not LHA preproorexin expression following RH, further potentially implicate PFH orexin neurons in the blunting of the behavioral response to RH.…”
Section: Discussionsupporting
confidence: 62%
“…This suggests a potential mechanism of hypoglycemia unawareness, i.e., diminished ability of hypoglycemia to stimulate arousal-promoting orexin neurons of the PFH, which are well described to be activated by hypoglycemia (5,6,22,34). Because PFH orexin neurons are implicated by the present findings in awareness of hypoglycemia, and by previous work in neurohumoral CRR to glucoprivation (29,37), they constitute a potentially important central neural substrate for mediating multiple components of hypoglycemia-associated autonomic failure. Orexin neurons, especially of the PFH, may contribute to behavioral responses during hypoglycemia, which are due to their activation during lowered glucose levels and which are independent of the symptoms caused by elevated Epi levels.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In particular, neurons found in the perifornical hypothalamus (PeH) and in the medulla. These neuronal groups communicate between themselves, are activated by hypoglycemia, and their activation is essential for counterregulatory hormonal and feeding responses (2)(3)(4)(5)(6). Furthermore, both groups indirectly communicate (ie, polysynaptically) with chromaffin cells in the adrenal medulla (7,8).…”
mentioning
confidence: 98%